EFEKTIFITAS MASSAGE TENGKUK TERHADAP PENINGKATAN JUMLAH AIR SUSU IBU NIFAS HARI PERTAMA SAMPAI HARI KETIGA DI PUSKESMAS WILAYAH BANTUL - Fika Pratiwi (STIKES Wira Husada Yogyakarta, 2019)
Breast milk is the most perfect baby food both in terms of quality and quantity through proper breastfeeding management. The achievement of exclusive breastfeeding in Indonesia in 2015 amounted to 55.7%. In Bantul regency, Yogyakarta, exclusive breastfeeding coverage of 74.73% still has not reached the national target of 80%. Problem that mostly occurs in the field is the mother who experienced disruption of breastfeeding in the first day until the third day. Nape massage and pectoralis major muscle massage have been shown to be good against breast milk production. However, there is no information about which type of the massages (both nape and the pectoralis major muscle massage) that is more effective in increasing the amount of breast milk.Objective: To know the effectiveness of nape massage in increasing breast milk quantity on women in childbed period from the first day to the third day in Bantul. Method: Pre-experiment, the static group comparison design. This research used a sample of 27 respondents of nape massage group and 27 respondents of pectoralis major muscle massage group. This research used Systematic Proportional Random Sampling for the sample collection technique. Massage was done once a day with the period of 15 minutes for 3 days. The data was analyzed by using Mann Whitney analysis method.Results: Most respondents were 21-23 years old and had a normal nutritional status. Most respondents had more than one child. Based on the statistical calculation, p-value of 0.000 (p <0.05) showed that the nape massage had significant effect in increasing breast milk quantity on women in childbed period from the first day to the third day in primaru healte care Bantul.Conclusion: statistically, this research proved that nape massage was more effective than pectoralis major muscle massage in increasing breast milk quantity on women in childbed period from the first day to the third day inprimari helath care Bantul.